TINGKAT INFEKSI EKTOPARASIT PADA IKAN TOMAN(Channa micropeltes) - Sri Herlina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This study aims to identify ectoparasites and determine the incidence of parasites in Toman fish that are kept in wooden cages in Muara Dua Village, Seruyan Hilir District, Seruyan Regency. The method of this research is the sampling of Toman fish (Channa micropeltes) as many as 60 fish taken from three cages where fish are kept using the survey method. Each fish was observed on the fins, skin and gills and compared the results with the identification key book. From the results of research on Toman fish originating from Muara Dua Village, it was found that 4 types of ectoparites that infested Toman fish were as follows: Ticodina sp, Dactylogrus sp, Oodinium sp, and Ichtyoptirius multifilis and predilection or sites of attack of ectoprasites including fins, skin, and gills with a level value of The incidence of ectoprasites ranges from 42-68%, including in the common and frequent categories.